Apex predator suppression is linked to restructuring of ecosystems via multiple ecological pathways. Issue 5 (21st December 2018) - Leo, Viyanna; Reading, Richard P.; Gordon, Christopher; Letnic, Mike
Abstract : Removal of apex predators can drive ecological regime shifts owing to compensatory positive and negative population level responses by organisms at lower trophic levels. Despite evidence that apex predators can influence ecosystems though multiple ecological pathways, most studies investigating apex predators' effects on ecosystems have considered just one pathway in isolation. Here, we provide evidence that lethal control of an apex predator, the dingo Canis dingo, drives shifts in the structure of Australia's tropical‐savannah ecosystems. We compared mammal assemblages and understorey structure at seven paired‐sites. Each site comprised an area where people poisoned dingoes and an area without dingo control. The effects of dingo control on mammals scaled with body size. Where dingoes were poisoned, we found greater activity of herbivorous macropods and feral cats, a mesopredator, but sparser understorey vegetation and lower abundances of native rodents. Our study suggests that ecological cascades arising from apex predators' suppressive effects on herbivores and mesopredators occur simultaneously. Concordant effects of dingo removal across tropical‐savannah, forest and desert biomes suggest that dingoes once exerted ubiquitous top–down effects across Australia and provides support for calls that top–down forcing should be considered a fundamental process governing ecosystem structure.